Comparison of the clinical outcomes of percutaneous kyphoplasty for the management of osteolytic and osteoblastic-related metastatic vertebral lesions. (2nd September 2021) - Wu, Wence; Zhang, Xinxin; Li, Xiaoyang; Liu, Huanmei; Xu, Libin; Liu, Ting; Yu, Shengji
Abstract : Objective: To retrospectively compare the clinical efficacy and safety of percutaneous kyphoplasty (PKP) for the management of osteolytic and osteoblastic-related metastatic vertebral lesions. Methods: A total of 117 patients with osteolytic (87 cases, 159 lesions, OL group) or osteoblastic-related (30 cases, 56 lesions, OB group) metastatic vertebral lesions underwent PKP. The clinical efficacy was assessed based on parameters including Visual Analog Scale (VAS), Oswestry Disability Index (ODI), vertebral body height (VBH) variation, and quality of life (QoL). Major and minor complications were systematically evaluated to assess the safety of the procedure. Results: No significant differences were found in the age, sex, or amount of bone cement between both groups (p>0.05). Compared with the OB group, the OL group was superior in operation duration (p<0.05) but was inferior in inflation pressure (p<0.05). Both groups experienced significant pain relief and improvement in the ODI, VBH, and QoL after PKP (p<0.05). The OB group had a better pain relief according to the VAS score but a poorer VBH restoration than the OL group throughout the follow-up period (p<0.05). No significant differences were observed in ODI and QoL between the two groups (p>0.05). The incidence of complications in the OL group was significantly higher than that in the OB group (p<0.05). Conclusions: PKP can safely achieve pain relief, functional improvement, VBH restoration, and QoL improvement for patients with osteolytic or osteoblastic-related metastatic vertebral lesions. Patients with osteolytic metastatic vertebral lesions showed better VBH restoration and had a shorter operation time but experienced less pain relief and had a greater incidence of complications than patients with osteoblastic-related metastatic vertebral lesions after PKP.